Implications of viral infections and oncogenesis in uterine cervical carcinoma etiology and pathogenesis - Chu, Daming; Liu, Tengteng; Yao, Yuan (Frontiers in Microbiology, 2023)
Background Uterine Cervical Carcinoma (UCC) is the most prevalent gynecological malignancy globally, with a rising incidence in recent years. Accumulating evidence indicates that specific viral infections, including human papillomavirus (HPV), Epstein-Barr virus (EBV), Hepatitis B and C viruses (HBV and HCV), and human herpesvirus (HHV), may contribute to UCC development and progression. Understanding the complex interplay between viral infections and UCC risk is crucial for developing novel preventative and therapeutic interventions. Methods This comprehensive review investigates the association between viral infections and UCC risk by examining the roles of various viral pathogens in UCC etiology and pathogenesis, and possible molecular mechanisms. Additionally, we evaluate current diagnostic methods and potential therapeutic strategies targeting viral infections for UCC prevention or treatment. Results The prevention of UCC has been significantly advanced by the emergence of self-sampling for HPV testing as a crucial tool, allowing for early detection and intervention. However, an essential challenge in UCC prevention lies in understanding how HPV and other viral coinfections, including EBV, HBV, HCV, HHV, HIV, or their concurrent presence, may potentially contribute to UCC development. The molecular mechanisms implicated in the association between viral infections and cervical cancer development include: 1) interference of viral oncogenes with cellular regulatory proteins, resulting in uncontrolled cell proliferation and malignant transformation; 2) inactivation of tumor suppressor genes by viral proteins; 3) evasion of host immune responses by viruses; 4) induction of a persistent inflammatory response, contributing to a tumor-promoting microenvironment; 5) epigenetic modifications that lead to aberrant gene expression; 6) stimulation of angiogenesis by viruses; and 7) activation of telomerase by viral proteins, leading to cellular immortalization. Additionally, viral coinfections can also enhance oncogenic potential through synergistic interactions between viral oncoproteins, employ immune evasion strategies, contribute to chronic inflammation, modulate host cellular signaling pathways, and induce epigenetic alterations, ultimately leading to cervical carcinogenesis. Conclusions Recognizing the implications of viral oncogenes in UCC etiology and pathogenesis is vital for addressing the escalating burden of UCC. Developing innovative preventative and therapeutic interventions requires a thorough understanding of the intricate relationship between viral infections and UCC risk.